Evolution and adjustments for the new rules in wrestling - Tünnemann, H. (International Journal of Wrestling Science, 2013)
Competition rules and their changes have a significant impact on training and competition strategies. Urgently necessary rule changes has been made by FILA with other changes during international competitions in May 2013. As a result of the application of the new rules can be stated that the introduction of the new rules were crowned principle of success: The new rules lead in all three disciplines in a significant increase in victories with technical superiority (ST , SP) at the expense of point victories. You caused an improvement of the performance index and the effectiveness of attack, which is reflected in the increase in activity and an enormous improvement in the attack oriented combat behavior. The number of realized technical points per bout increased in all three disciplines of the rule changes. The formal appreciation of 2-point ratings lead to a reduction of the 1-point ratings but not to increase the 3 - and 5 - point votes values or to an increase of the pins what cannot be seen as an increase of attractiveness . This is also the occasion for further reflection and for an extensive evaluation of the Senior World Championships in Budapest.